Distribution and Mechanism of ?-Amanitin Tolerance in Mycophagous Drosophila (Diptera: Drosophilidae). - Stump, A.D.; Jablonski, S.E.; Bouton, L.; Wilder, J.A. (Environmental Entomology, 2011)
Many mycophagous species of Drosophila can tolerate the mushroom poison ?-amanitin in wild mushrooms and in artificial diet. We conducted feeding assays with sixteen Drosophila species and ?-amanitin in artificial diet to better determine the phylogenetic distribution of this tolerance. For eight tolerant and one related susceptible species, we sequenced the gene encoding the large subunit of RNA Polymerase II, which is the target site of ?-amanitin. We found no differences in the gene that could account for differences in susceptibility to the toxin. We also conducted feeding assays in which ?-amanitin was combined with chemical inhibitors of cytochrome P450s or glutathione S-transferases (GSTs) in artificial diet to determine if either of these enzyme families is involved in tolerance to ?-amanitin. We found that an inhibitor of GSTs did not reduce tolerance to ?-amanitin, but that an inhibitor of cytochrome P450s reduced tolerance in several species. It is possible that the same cytochrome P450 activity that produces tolerance of ?-amanitin might produce tolerance of other mushroom toxins as well. If so, a general detoxification mechanism based on cytochrome P450s might answer the question of how tolerance to ?-amanitin arose in mycophagous Drosophila when this toxin is found in relatively few mushrooms.